Desain Komunikasi Visual Sebagai Media Penunjang Informasi Pada Event RAKER XII Perguruan Tinggi Raharja - Lusyani Sunarya; Devy Rositarini; Riska Andriyanti (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
Event is a communication media is a bridge to present the intent or purpose of the event to a specifictarget. In this era, many held as a media event promotion or information. Perguruan tinggi raharja isan institution that specializes in computer-based education in their orientation. The universityannually hosts Prog event held on a regular basis in accordance with the schedule of the academiccalendar of events that is RAKER XII. In an event, Visual Communication Design is one of the basicneeds as a means of delivering information from an event. Procurement event held usually requiresvarious forms of media with messages that are up to date and clear, and it requires a new designnuances each year. Elements such as the media information needed an event such as the introductionof an event in accordance with the expected mission. Media information that is used in the form ofevent RSKER Banner Family Gathering XII Meeting XII Meeting XII Banner, Banner Raker XII(Excellence), XII Meeting banners, Banner Theme Raker, Banner Welcome Raker XII, Pin Joint andReconnaissance Raker XII, banners bottom RAKER, Cover Book RENSTRA. Through design DesignXII Meeting is expected as well as the success of the event will support the XII Meeting on PerguruanTinggi Raharja, and improve the image of Perguruan Tinggi Raharja in order to be better knownProg wide community.